Meningkatkan Minat Literasi Membaca dan Keterampilan Berpikir Kritis Siswa Menggunakan Kombinasi Model PBL, Inkuiri, dan TGT di SDN Kelayan Selatan 10 Banjarmasin - Mutia Azizah; Metroyadi . (CV. ITTC INDONESIA, 2024)
This research used Classroom Action Research (CAR) which was carried out in 4 meetings. This research uses a qualitative approach, the data taken is qualitative data obtained through observing teacher activities, student activities, literacy interests, critical thinking skills, then using quantitative data for student learning outcomes obtained through group and individual written tests. The subjects of this research were 23 students in class IV of SDN Kelayan Selatan 10, Banjarmasin City, consisting of 13 male students and 10 female students. Semester II 2023/2024 academic year. The results of this research show that teacher activity at meeting I got a score of 21, at meeting IV got a score of 27. Student activity at meeting I was still 61%, increasing at meeting IV to 96%. Interest in reading literacy at meeting I was still 57%, increasing at meeting IV to 96%. Critical thinking skills at meeting I were still 43%, increasing at meeting IV to 91%. Student learning outcomes at meeting I were 43%, increasing at meeting IV with classical completeness at 96%. This research concludes that the use of a combination of Problem Based Learning, Inquiry and Team Games Tournament models can improve the quality of teacher activities, student activities, interest in reading literacy, critical thinking skills and student learning outcomes. It is recommended that the Problem Based Learning, Inquiry, and Team Games Tournament models can be used as alternative references in improving the quality of teacher activities, student activities, interest in reading literacy, critical thinking skills, and student learning outcomes